Enhancing Efficiency in Traditional Travel Agencies: The Implementation of Blockchain Technology at Astrindo Satrya Kharisma - Mohamad Rifki Dimas Putra; Isti Raafaldini Mirzanti (Siber Journal of Advanced Multidisciplinary, 2026)
Traditional B2B travel agencies in emerging markets continue to rely on manual, intermediary-heavy workflows despite increasing digitalization in the tourism sector. This study examines how blockchain technology can address operational inefficiencies at Astrindo Satrya Kharisma, an Indonesian travel agency specializing in group tours and MICE services. Using a qualitative case-study approach, data were collected through semi-structured interviews with the Operational Manager and a corporate client, supported by internal document analysis. A fishbone (Ishikawa) analysis identified the root causes of inefficiencies, while Rashideh’s (2020) blockchain disintermediation framework was used to evaluate the relevance of five blockchain features: decentralization, trust, security, cost reduction, and speed. The findings reveal that Astrindo’s operational challenges stem primarily from low traceability, reflected in limited real-time transaction visibility, inconsistent stakeholder communication, and repetitive administrative processes. To address these issues, a four-phase, twelve-month private blockchain implementation roadmap is proposed, beginning with a pilot involving selected vendors and client accounts before scaling to smart-contract automation of booking confirmation, payment verification, and document management. The study demonstrates that blockchain can function as a structural mechanism for improving traceability and coordination across fragmented B2B travel service chains.